A chromosome-scale reference genome and integrative transcriptome provide insight into tissue- and stress-specific responses in tetraploid sainfoin (Onobrychis viciifolia) - Cuong V. Nguyen; Dustin Cram; Halim Song; Rodrigo Ortega Polo; Hari Poudel; Bill Biligetu; Kimberley Burton Hughes; Surya Acharya; David Konkin; Stacy D. Singer (Planta, 2026)
Main conclusion A haplotype-resolved, chromosome-scale AAC Mountainview sainfoin genome sequence along with organelle assemblies, methylome, and comparative tissue/stress-specific transcriptomes provide a solid foundation to support downstream sainfoin breeding efforts. Abstract Sainfoin ( Onobrychis viciifolia Scop.) is an outcrossing, perennial forage crop valued for its leguminous nature, nutritional quality, palatability, and production of condensed tannins, which reduce the incidence of pasture bloat in ruminants and improve feed efficiency. However, despite its potential, there remains a paucity of research and breeding efforts focusing on this species. In this study, we report the generation of a haplotype-resolved, chromosome-scale reference genome sequence for a genotype of the tetraploid sainfoin cultivar AAC Mountainview, which was assembled using PacBio HiFi, Oxford Nanopore, Illumina short read, and Hi-C data. The 2.36 Gb assembly resolves all 28 pseudochromosomes, corresponding to 4 haplotypes of the 7 base chromosomes, with high contiguity and gene completeness, as well as reference-grade long terminal repeat (LTR) assembly index (LAI) scores across all haplotypes. Nanopore-based methylation profiling revealed typical gene body CG methylation, as well as high levels of transposable element methylation. We annotated 117,890 high-confidence protein-coding genes and identified large tandem arrays of rDNA localized on unanchored but chromosome-associated scaffolds. Mitochondrial and chloroplast genomes were also successfully assembled for this genotype. Furthermore, tissue- and stress-specific transcriptomic profiling revealed both shared and distinct gene expression responses across tissue and stress types. Allele-specific expression analysis showed largely balanced haplotype activity, with subtle but consistent shifts in allelic dominance under stress. The data provided in this study offer a valuable resource for downstream breeding endeavors in this promising forage crop.

In-depth analysis of ambient air pollution changes due to the COVID-19 pandemic in the Asian Monsoon region - Mohd Talib Latif; Noorain Purhanudin; Nur Zulaikha Mohd Afandi; Maria Obiminda L. Cambaliza; Nor Diana Abdul Halim; Nor Syamimi Sufiera Limi Hawari; To Thi Hien; Ohnmar May Tin Hlaing; Warnakulasuriya Roshani Loreta Hiranthi Jansz; Muhammad Fahim Khokhar; Puji Lestari; Shih-Chun Candice Lung; et al. (Science of The Total Environment, 2024)

Recent Progress in Engineering Mesenchymal Stem Cell Differentiation - Alexander Halim; Agnes Dwi Ariyanti; Qing Luo; Guanbin Song (Stem Cell Reviews and Reports, 2020)